Effect of an educational intervention on health literacy and hope in patients with myocardial infarction - Zahra Molazem; Ziba Rostampour; Pouran Tavakoli; Roya Dokoohaki; Parvin Ghaemmaghami (Scientific Reports, 2026)
Abstract This study aimed to investigate the effect of an educational intervention on health literacy and hope in patients with heart attack hospitalized in the Cardiac Intensive Care Units of Hospital in Shiraz, Iran. This experiment involved the use of a parallel group single blind randomized controlled clinical trial performed in six cardiac intensive care units in Shiraz University of Medical Sciences, Iran. The six cardiac intensive care units were randomly divided into two experimental groups (three units for each group), so that information contamination could be minimized. Overall, 124 subjects participated in the study (mean age was 55.12 ± 10.19 years, 79.8% male). Before the intervention, both groups completed the Montazeri Health Literacy and Snyder Hope questionnaires. The intervention group received a structured educational program, which consisted of three individual, face-to-face sessions during hospitalization, followed by one month of post-discharge virtual education via WhatsApp and weekly telephone follow-ups. The control group received only the routine ward education. One-month post-intervention, the questionnaires were re-administered to both groups. Data were analyzed using SPSS software (version 26) with appropriate statistical tests. The results indicated that before the intervention, the mean health literacy and hope scores were similar between the experimental and control groups. After the intervention, a significant increase in the mean health literacy scores was observed in the intervention group compared to the control group ( p < 0.001 Although the intervention group showed a slight increase in hope scores, this change was not statistically significant. ( p > 0.05). However, the educational intervention proved effective in improving the health literacy of participants by a significant margin. Although there was no significant improvement in the hope levels in the intervention group, the intervention managed to prevent the marked decrease in the hope levels in the control group. It is therefore recommended that educational interventions be incorporated into post-discharge care in cases of myocardial infarction. Trial registration This trial was registered in the Iranian Registry of Clinical Trials (IRCT code: IRCT20250427065490N1. 2025.05.14).